Hyperpolarisation of Mirfentanil by SABRE in the Presence of Heroin. Issue 11 (11th May 2021) - Robertson, Thomas B. R.; Gilbert, Nicolas; Sutcliffe, Oliver B.; Mewis, Ryan E.
Abstract: Mirfentanil, a fentanyl derivative that is a μ ‐opioid partial agonist, is hyperpolarised via Signal Amplification By Reversible Exchange (SABRE), a para ‐hydrogen‐based technique. [Ir(IMes)(COD)Cl] (IMes=1, 3‐ bis (2, 4, 6‐trimethylphenyl)imidazole‐2‐ylidene, COD=cyclooctadiene) was employed as the polarisation transfer catalyst. Following polarisation transfer at 6.5 mT, the pyrazine‐protons were enhanced by 78‐fold (polarisation, P=0.04 %). The complex [Ir(IMes)(H)2 (mirfentanil)2 (MeOH)] + is proposed to form based on the observation of two hydrides at δ −22.9 ( trans to mirfentanil) and −24.7 ( trans to methanol). In a mixture of mirfentanil and heroin, the former could be detected using SABRE at concentrations less than 1 % w/w. At the lowest concentration analyzed, the amount of mirfentanil present was 0.18 mg (812  μ M) and produced a signal enhancement of −867‐fold (P=0.42 %). following polarisation transfer at 6.5 mT. Abstract : Mirfentanil detection : Mirfentanil, a fentanyl derivative and μ ‐opioid partial agonist, is hyperpolarised via the hyperpolarisation technique Signal Amplification By Reversible Exchange (SABRE). In a series of simulated samples consisting of mirfentanil and heroin, the amount of mirfentanil was varied from 0.63 % w/w–3.80 % w/w. Mirfentanil was readily detected in the 1 H NMR spectrum (single transient) at all the concentrations studied when SABRE was employed.